Intracranial extramedullary hematopoiesis in a thalassemic girl: A Case report - Varshney, Arpita; Barwa, Vikas; Saini, Lalit; Lamba, Preeti; Yadav, Rohtas K (Indian Journal of Case Reports, 2017)
Beta-thalassemia is a haemolytic disorder with ineffective erythropoiesis and red blood cell destruction. Extramedullary hematopoiesis is one of the complications associated with beta-thalassemia. Extramedullary hematopoiesis is the ectopic production of blood cells outside the marrow in liver, spleen, lymph nodes and many other sites. Intracranial involvement is extremely rare. We report a case of 17-year-old girl with thalassemia major and intracranial extramedullary hematopoiesis who came with the complaints of seizure, headache and generalised weakness. Imaging and blood profile leads to the final diagnosis with MRI playing a key role and patient was managed successfully. With this report, we discuss the imaging findings of intracranial extramedullary hematopoiesis in details.